Clinical governance and internal medicine: a marriage of convenience? - Vincenzo Nuzzo; Emanuela Foglia; Tiziana Attardo; Clelia Canale; Mariangela Di Lillo; Lorenzo Fiorin; Micaela La Regina; Ada Maffettone; Domenico Montemurro; Antonino Mazzone; for the Master Course in Clinical Governance (Italian Journal of Medicine, 2015)
Amplification in health expectations, increase in new technologies, decrease in economic resources and the breakdown of traditional control systems have led to the development of clinical governance (CG). The aim of the present pilot study was to investigate the application of CG tools in significant sample of Italian internal medicine wards (IMW). A 37-item questionnaire was developed and administered to 39 physicians, within 33 IMWs throughout Italy. Thanks to the data analysis, the perceived usefulness, the utilization rate of CG tools, the correlations between CG use, wards characteristics, and/or localization were studied. We identified at what organizational level the CG tools were applied and used. fifty-two percent of the studied tools were being used in the investigated hospitals. The average utility and utilization rate was different depending on the region of provenance. This research showed that CG is a methodology often used by Italian hospitals physicians, especially for inpatient care. The encouraging results of this pilot study could suggest opportunities to extend the survey at national level, to generalize the results.